Lifestyles of nursing students from a colombian public university (2016)
ABSTRACT: To assess the lifestyles of nursing students from a Colombian public university. Methods. A cross-sectional study was conducted in 2014. 380 students answered by self-reporting the adapted version in Spanish of FANTASTIC Lifestyles Assessment Questionnaire of Wilson and Ciliska. Results. Lifestyles were poor in 9.2%, fair in 31.3%, good in 53.7%, and excellent in only 5.8% of the participants. Statisticallysignificant differences of the total mean score were not found when comparing with gender, age group, and course year, but were detected in two domains by gender: a) physical activity (higher score in men) and b) cigarette smoking (higher score in women). Conclusion. An important proportion of our nursing students has inadequate lifestyles, which means deferred risks for the development of chronic diseases. Universities should promote the training of the future professionals in nursing with knowledge and skills aimed at healthy lifestyles.